IMPROVING ORGANIZATIONAL WORK PROCESS OF LAND REGISTRATION BASED ON 3D CADASTRE AND CADASTRE 2014 CONCEPTS (Case Study Apartment Unit Registration) - M Arif Suhattanto (BHUMI: Jurnal Agraria dan Pertanahan, 2013)
The need for land always increases but the area of land never increases. This makes people to use the landeffectively. The use of traditional cadastre; the use of 2 dimensional cadastral concept, is no longer able to fulfill the completecadastral needs. Having experiments on applying the 2 dimensional land registration, knowledge on 2014 cadastral conceptsand 3 dimensional cadastral concepts, the development of the ongoing organization’s work process is badly required. The paperis aimed at explaining how to design the process of land registration in applying the 3 D cadastral and 2014 cadastral conceptsusing a modeling process. The result of the process is the new diagram showing the change of the organization; both inside andoutside. However, due to the complexity of the 3 D cadastral concept, the discussion is limited to the apartment units inIndonesia.Keywords: 3D cadastre, 2014 cadastre, modeling.